2020
DOI: 10.1177/1055665620982807
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Number of Surgeries and Parent Ratings of Academic and Behavioral Functioning Among Children With Isolated Oral Clefts

Abstract: Objective: The purpose of this study was to evaluate possible relationships between number of surgeries and parent ratings of academic functioning among children with isolated oral clefts. Design: Multicenter, retrospective cohort study including structured interviews, questionnaires, and chart reviews. Setting: Completion of questionnaires occurred during clinical visits at 6 different cleft centers across North America. Participants: Parents of 285 children with isolated clefts of the lip and/or palate, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Similarly, Conrad et al's questionnaire-based study found that white race was predictive of better parent-reported functioning, despite controlling for the amount of surgeries undergone. 31…”
Section: Race and Ethnicitymentioning
confidence: 99%
“…Similarly, Conrad et al's questionnaire-based study found that white race was predictive of better parent-reported functioning, despite controlling for the amount of surgeries undergone. 31…”
Section: Race and Ethnicitymentioning
confidence: 99%
“…In patients with congenital anomalies, orthognathic surgery is one of a series of procedures over the course of their development, along with additional multidisciplinary treatment, and the history of complex care can be a psychosocial risk factor. For example, a greater number of surgeries has been linked to parental report of lower social and activity participation in children with a cleft 10 . The complexity of craniofacial care is also important to consider because trauma exposure before orthognathic treatment was found to be a risk factor for developing dental anxiety and PTSD symptoms 11 .…”
mentioning
confidence: 99%
“…For example, a greater number of surgeries has been linked to parental report of lower social and activity participation in children with a cleft. 10 The complexity of craniofacial care is also important to consider because trauma exposure before orthognathic treatment was found to be a risk factor for developing dental anxiety and PTSD symptoms. 11 In addition, orthognathic surgeries occur in late adolescence or early adulthood, which is a developmental period of emerging independence that can make the treatment course challenging.…”
mentioning
confidence: 99%